2021
DOI: 10.1002/nano.202100117
|View full text |Cite
|
Sign up to set email alerts
|

Improved CsPbBr3 visible light photodetectors via decoration of sputtered au nanoparticles with synergistic benefits

Abstract: Owing to the intense carrier recombination and limited optical absorption, the as‐fabricated CsPbBr3 visible light photodetectors (PDs) are far from practical application. In this work, we have demonstrated performance‐improved metal‐semiconductor‐metal (MSM) structured CsPbBr3 visible light PDs realized by the decoration of sputtered Au nanoparticles (NPs). It showed that the Au NPs on the CsPbBr3 exhibited synergistic benefits including improving the photogenerated charge carriers’ lifetime and enhancing the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 63 publications
(77 reference statements)
0
10
0
Order By: Relevance
“…Specifically, the on–off ratio, which is defined as the ratio of photocurrent (defined as the current captured under illumination) to dark current, is ∼55 under the 540 nm illumination with a power of ∼50 nW (Figure b). As reported before, the efficient photoresponse of the MSM-structured PDs is mainly associated with the high optical absorption coefficient and efficient charge carrier transport of the all-inorganic CsPbBr 3 . , However, the MSM-structured PD shows a poor stability. In detail, the dark current rapidly increases with the increase in the pulse number (a pulse means a cycle of switching on and off the incident light, as shown in Figure a inset), as shown in Figures a and S6 (Supporting Information).…”
Section: Resultsmentioning
confidence: 60%
See 3 more Smart Citations
“…Specifically, the on–off ratio, which is defined as the ratio of photocurrent (defined as the current captured under illumination) to dark current, is ∼55 under the 540 nm illumination with a power of ∼50 nW (Figure b). As reported before, the efficient photoresponse of the MSM-structured PDs is mainly associated with the high optical absorption coefficient and efficient charge carrier transport of the all-inorganic CsPbBr 3 . , However, the MSM-structured PD shows a poor stability. In detail, the dark current rapidly increases with the increase in the pulse number (a pulse means a cycle of switching on and off the incident light, as shown in Figure a inset), as shown in Figures a and S6 (Supporting Information).…”
Section: Resultsmentioning
confidence: 60%
“…In the past few years, various kinds of LHP materials such as polycrystalline films, nanowires, microcrystals, and single crystals (i.e., bulk materials) have been explored to fabricate the visible light photodetectors (PDs). Among them, the LHP single crystals are generally preferred because of their improved crystalline quality and low density of defects, both of which are fundamental for the fabrication of performance-improved PDs. Notably, it showed that the density of defects in the solution-grown LHP single crystals was only ∼10 9 –10 11 cm –3 , which is about 6–7 orders of magnitude less than that in their polycrystalline films. The ultralow concentration of defects guarantees the as-fabricated PDs with a low dark current and produces a high photoresponsivity to the light signal simultaneously. Very recently, we have demonstrated the growth of high crystalline quality all-inorganic perovskite CsPbBr 3 single crystals via a modified low-temperature one-step solution growth method, in which the defects were shown as low as ∼10 9 cm –3 . , On this basis, Au/CsPbBr 3 /Au metal–semiconductor–metal (MSM)-structured visible light PDs have been fabricated with the photoresponsivity of 0.088 A/W .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…; B = Pb; X = Cl, Br, and I) featured with superior optoelectrical properties such as long charge carrier diffusion length, high optical absorption coefficient, and low‐temperature solution‐processed ability, have been widely regarded as important candidates for the fabrication of high‐performance PDs. [ 10–13 ] In recent years, heterojunction PDs combining the LHP films and other semiconductors (such as ZnO, [ 14 ] TiO 2 , [ 15 ] SnO 2 , [ 16 ] CdS, [ 17 ] and Si [ 18,19 ] ) have been fabricated, in which high‐performance self‐powered photodetection has been demonstrated. Among them, the fabrication of self‐powered PDs combining the LHP and Si materials is necessary and meaningful due to the unassailable position of Si in optoelectronics and microelectronics.…”
Section: Introductionmentioning
confidence: 99%